The origins of the Roman cult of Mithras in the light of new evidence and interpretations: the current state of affairs - Chalupa, Aleš (Religio, 2016)
This article deals with the still unresolved question of the origins of the Roman cult of Mithras. After a brief history of the scholarship dealing with this topic, individual mithraea, inscriptions, and passages in literary texts which have been dated to the earliest period of the cult's existence are evaluated. On the basis of this re-evaluation, some provisional conclusions concerning the question of Mithraic origins are made, namely that (1) the earliest evidence comes from the period 75-125 CE but remains, until the second half of the 2nd century CE, relatively negligible; (2) the geographical distribution of early evidence does not allow for a clear identification of the geographical location from which the cult started to spread, which suggests that (3) the cult made effective use of Roman military infrastructure and trade routes and (4) was transmitted, at least initially, due to the high mobility of the first propagators. However, it must be acknowledged that, at present, we can neither conclusively identify its place of origin nor the people who initiated the cult. In addition it is impossible to describe the specific historical circumstances in which these formative processes should be placed.